Daniel K. Inouye Solar Telescope: High‐resolution observing of the dynamic Sun. Issue 10 (November 2016) - Tritschler, A.; Rimmele, T. R.; Berukoff, S.; Casini, R.; Kuhn, J. R.; Lin, H.; Rast, M. P.; McMullin, J. P.; Schmidt, W.; Wöger, F.; DKIST Team
Abstract: The 4‐m aperture Daniel K. Inouye Solar Telescope (DKIST) formerly known as the Advanced Technology Solar Telescope (ATST) is currently under construction on Haleakalā (Maui, Hawai'i) projected to start operations in 2019. At the time of completion, DKIST will be the largest ground‐based solar telescope providing unprecedented resolution and photon collecting power. The DKIST will be equipped with a set of first‐light facility‐class instruments offering unique imaging, spectroscopic and spectropolarimetric observing opportunities covering the visible to infrared wavelength range. This first‐light instrumentation suite will include: a Visible Broadband Imager (VBI) for high‐spatial and ‐temporal resolution imaging of the solar atmosphere; a Visible Spectro‐Polarimeter (ViSP) for sensitive and accurate multi‐line spectropolarimetry; a Fabry‐Pérot based Visible Tunable Filter (VTF) for high‐spatial resolution spectropolarimetry; a fiber‐fed Diffraction‐Limited Near Infra‐Red Spectro‐Polarimeter (DL‐NIRSP) for two‐dimensional high‐spatial resolution spectropolarimetry (simultaneous spatial and spectral information); and a Cryogenic Near Infra‐Red Spectro‐Polarimeter (Cryo‐NIRSP) for coronal magnetic field measurements and on‐disk observations of, e.g., the CO lines at 4.7 μm. We will provide an overview of the DKISTs unique capabilities with strong focus on the first‐light instrumentation suite, highlight some of the additional properties supporting observations of transient and dynamic solar phenomena, and touch on some operational strategies and the DKIST critical science plan. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)